2021
DOI: 10.3390/cells10102523
|View full text |Cite
|
Sign up to set email alerts
|

The HPSE Gene Insulator—A Novel Regulatory Element That Affects Heparanase Expression, Stem Cell Mobilization, and the Risk of Acute Graft versus Host Disease

Abstract: The HPSE gene encodes heparanase (HPSE), a key player in cancer, inflammation, and autoimmunity. We have previously identified a strong HPSE gene enhancer involved in self-regulation of heparanase by negative feedback exerted in a functional rs4693608 single-nucleotide polymorphism (SNP) dependent manner. In the present study, we analyzed the HPSE gene insulator region, located in intron 9 and containing rs4426765, rs28649799, and rs4364254 SNPs. Our results indicate that this region exhibits HPSE regulatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…In previous studies, we identified two regulatory regions of the HPSE gene, a strong enhancer, located in intron 2 [ 20 ], and a 200 bp insulator mapped in intron 9 [ 21 ]. The number of functional SNPs in both regulatory regions and their interactions were characterized [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, we identified two regulatory regions of the HPSE gene, a strong enhancer, located in intron 2 [ 20 ], and a 200 bp insulator mapped in intron 9 [ 21 ]. The number of functional SNPs in both regulatory regions and their interactions were characterized [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we identified two regulatory regions of the HPSE gene, a strong enhancer, located in intron 2 [ 20 ], and a 200 bp insulator mapped in intron 9 [ 21 ]. The number of functional SNPs in both regulatory regions and their interactions were characterized [ 21 ]. The enhancer rs4693608 SNP has a major impact on HPSE gene expression and the risk of acute graft-versus-host disease (GVHD) after hematopoietic stem cell transplantation (HSCT).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations